EFFECTIVENESS OF MULTIFACTOR AUTHENTICATION TECHNOLOGY FOR PROTECTING STUDENT PRIVACY : A SYSTEMATIC LITERATURE REVIEW - Cahyanto, Iman; Madihah, Husnul; Budiarso, Iwan; Sutrisno, Andy; Hidayat, Tofan (Universitas Wiralodra, 2024)
Student privacy is a major concern in the digital era, especially with the increasing use of educational technologies such as Learning Management Systems (LMS) and IoT devices. Traditional authentication systems are considered inadequate in the face of complex security threats. Therefore, this study evaluates the effectiveness of Multi-Factor Authentication (MFA) in protecting student privacy in an educational environment. This study uses a Systematic Literature Review (SLR) design based on 86 relevant articles selected from Scopus indexed journals (2020–2024). The articles were analyzed thematically using PRISMA Flow Diagram to identify patterns, trends, and gaps related to MFA implementation. The findings show that MFA can improve student privacy protection by reducing the risk of data leaks by up to 80%, lowering unauthorized access, and increasing user trust. Key technologies include biometrics, OTP, and blockchain, which have proven to be effective in improving security. However, MFA implementation faces obstacles such as cost, system complexity, and biometric data privacy concerns. This research makes an important contribution to academic literature and educational data security practices. Recommendations for further research include the exploration of behavior-based authentication methods, studies on user perception, and the implementation of MFA in educational environments with limited infrastructure. The practical implications include strengthening technology security policies in educational institutions and educating users to raise awareness of the importance of data privacy protection. Keywords: Student privacy, Multi-Factor Authentication (MFA), Educational Data Security, Biometric Technology